Pengaruh Metode Ceramah dan Metode Diskusi Terhadap Hasil Belajar Siswa Kelas X Jurusan Bisnis Daring Pemasaran di SMK Negeri 2 Tondano - Devid Aring; Johny Taroreh; Niny Makaliwe (Edupreneurship: Jurnal Pendidikan Ekonomi, 2026)
This study was conducted with the aim of analyzing the extent to which the application of the lecture method influences the learning outcomes of class X students in the Online Business and Marketing (BDP) expertise competency at SMK Negeri 2 Tondano. In addition, this study is also directed to examine the impact of the use of discussion methods on student academic achievement in the scope of similar classes and majors, as well as identifying how the combination of lecture and discussion methods simultaneously affects student grades in the subject of Marketing Basics for class X BDP Department of SMK Negeri 2 Tondano. A quantitative approach with a survey design was applied in this research methodology. The primary data collection was obtained directly from respondents who were designated as samples, using a questionnaire as the main instrument. The population in this study included 48 class X BDP Department students at SMK Negeri 2 Tondano. The sampling technique used was simple random sampling with a precision level or margin of error of 5%, resulting in a sample size of 43 students. The findings from the data testing showed that the lecture method had a positive and quite essential influence on improving the learning outcomes of class X BDP Department students at SMK Negeri 2 Tondano. Furthermore, the application of the discussion method has also been shown to contribute significantly to student academic achievement in the class and department. Furthermore, the combined use of lecture and discussion methods has demonstrated a positive and tangible impact on the learning outcomes of 10th-grade students in the Education and Training Department at SMK Negeri 2 Tondano.